Revisiting the presumptions of resulting trust and advancement in the context of joint tenanted matrimonial property: Two innovations by the Singapore Court of Appeal - MAH, Ian Hao Ran (Institutional Knowledge at Singapore Management University, 2020)
In Singapore, the Court of Appeal’s decision in Lau Siew Kim v Yeo Guan Chye Terence remains the most authoritative pronouncement on the operation of the presumptions of resulting trust and advancement, particularly in the context of joint tenanted matrimonial property. One notable, albeit often overlooked, aspect of the decision is the modification of the presumption of advancement to operate like a rule of survivorship. On one view, the effect of this is to retransform the equitable tenancy in common into an equitable joint tenancy. This article identifies the doctrinal difficulties with this approach but ultimately recommends that the same result, which is merited, can be more directly achieved by employing the maxim ‘equity follows the law’. Jurisdictions seeking to formulate a coherent approach to the ever-confusing area of joint tenancy can draw from the approach taken by Singapore’s apex court.